Corrosion and Passivation of High Nitrogen Face-Centered-Cubic Phase Formed on AISI 304L Austenitic Stainless Steel in Borate Buffer Solution. Issue 10 (1st January 2015) - Wang, K. S.; Tong, S.; Lei, M. K.
Abstract : The corrosion behavior of a high nitrogen face-centered-cubic (f.c.c.) phase (γN ) formed on plasma-based low-energy nitrogen ion implanted AISI 304L austenitic stainless steel in a borate buffer solution with a pH value of 8.4 was investigated by using anodic polarization, electrochemical impedance spectroscopy, Mott-Schottky analysis and Auger electron spectroscopy/x-ray photoelectron spectroscopy. Compared with original austenitic stainless steel, the γN phase layer on austenitic stainless steel possessed a significant improvement in corrosion resistance in the borate buffer solution with an apparent decrease of passivation current density and an increase of corrosion potential. A larger electrochemical impedance with a maximal phase angle of the 83° over low frequency range was obtained for the γN phase layer. The donor and acceptor densities of the γN phase layer and the corresponding flat band potential decreased, relative to that of original austenitic stainless steel. The protective passive film on the γN phase layer was observed as n -type and p -type semiconductors in the potential range above and below the flat band potential, respectively. It was composed of hydroxide/oxides of iron and chromium in the outer region and oxides of chromium and iron in the inner region both accompanied by chromium and iron nitrides, unlike original stainless steel which had pure iron and chromium on outermost surface. The calculated passive film thickness of 2.82 ± 0.67 nm on the γN phase layer by the power law distribution was compared with the measured thickness of 6.5 nm by AES/XPS. The improvement mechanism of nitrogen atoms in the γN phase layer on corrosion properties in the borate buffer solution was proposed by means of an applied point defect model.